Розробка системи моніторингу та контролю процесу відведення фільтраційних вод від земляних гребель - Таргоній, Іван; Сафоник, Андрій; Пилипенко, Володимир (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Розглянуто систему відведення фільтраційних вод на гідроенергетичних об’єктах. Розроблено автоматичну системи розрахунку витрати фільтраційного потоку для непідтопленого водоміру з індикацією рівнів рідини, архівуванням даних в SCADA системі. <pre id="tw-target-text" class="tw-data-text tw-text-large tw-ta" dir="ltr" data-placeholder="Переклад" data-ved="2ahUKEwjTnN_xnKKJAxXGUXcKHbl0IfUQ3ewLegQIBxAU" aria-label="Перекладений текст: The filtration water removal system at hydropower facilities is considered. An automatic system for calculating the filtration flow rate for a non-flooded water meter with liquid level indication, data archiving in the SCADA system has been developed.">The filtration water removal system at hydropower facilities is considered. An automatic system for calculating the filtration flow rate for a non-flooded water meter with liquid level indication, data archiving in the SCADA system has been developed.